The Universal Periodic Review: A Catalyst for Domestic Mobilisation. Issue 4 (2nd October 2022) - Lane, Michael
ABSTRACT: At its introduction in 2006, scholars were sceptical of the United Nations (UN) Universal Periodic Review (UPR), doubting whether its cooperative, 'soft law' approach would be able to affect positive changes to states' human rights practices. Yet research on its three cycles to date is replete with evidence of the mechanism's impact. What accounts for this? The theory of acculturation, which highlights states' socialisation, is the most salient explanation posed in UPR scholarship. This article argues that while acculturation is an otherwise compelling account, it fails to recognise the vital role domestic actors play in affecting state compliance and, particularly, the success of the UPR. The domestic mobilisation theory, which emphasises the influence of national politics and players on compliance, is forwarded as an alternative lens through which to grasp the UPR's impact. A review of existing research on the UPR reveals the mechanism to be a catalyst for mobilisation, providing leverage and an opportunity for dialogue between domestic actors and governments. Appreciating the UPR's value in this way has implications for scholars and practitioners engaging it.